Characteristics of the gut microbiome in patients with prediabetes and type 2 diabetes - Zewen Zhang; Tian Tian; Zhen Chen; Lirong Liu; Tao Luo; Jianghong Dai (PeerJ, 2021)
Background Gut microbiome has recently been identified as a new potential risk factor in addition to well-known diabetes risk factors. The aim of this study was to analyze the differences in the composition of gut microbiome in prediabetes(PreDM), type 2 diabetes mellitus (T2DM) and non-diabetic controls. Methods A total of 180 participants were recruited for this study: 60 with T2DM, 60 with PreDM and 60 non-diabetics (control group). Fecal samples were collected from the participants and genomic DNA was extracted. The composition and diversity of gut microbiome were investigated in fecal DNA samples using Illumina sequencing of the V3∼V4 regions of 16sRNA. Results There were significant differences in the number of bacteria among patients with PreDM and T2DM and the control group. Compared with the control group, Proteobacteria bacteria were significantly higher in the PreDM group (P = 0.006). On the genus level, Compared with the control group, the relative abundance of Prevotella and Alloprevotella was significantly higher in the T2DM group (P = 0.016, P = 0.018), and the relative abundance of Paraprevotella in T2DM and PreDM groups was lower than that in the control group (P = 0.011, P = 0.045). Compared with the PreDM group and the control group, the relative abundance of Bacteroides in the T2DM group was significantly lower (P = 0.019, P = 0.002). Conclusions The present study found significant differences in the gut microbiome between PreDM, T2DM and non-diabetic individuals, specifically at the genus level, suggesting that early intervention in PreDM patients could have implications for gut flora transitioning to T2DM. In addition, these results may be valuable for developing strategies to control T2DM by modifying the gut microbiome.